2022
DOI: 10.3390/economies10020037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inflation Targeting (IT) Policy on the Inflation Uncertainty and Economic Growth in Selected African and European Countries

Abstract: The study assessed the effect of inflation targeting (IT) policy on inflation uncertainty and economic growth in African and European IT countries. This study contributes to the existing knowledge by analysing and comparing the African IT and European IT countries using two advanced approaches which include the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) and Panel Vector Autoregressive (PVAR). To determine how the IT policy affects the inflation uncertainty in selected countries, time ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
2
5
2
Order By: Relevance
“…The results of this study show that there are different influences of the IT regime in terms of its influence on the GDP growth rate that are in line with the results obtained by S. T. Nene, D. I. Kehinde and S. Mashapa (2022) in their research done in the selected European and African countries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study show that there are different influences of the IT regime in terms of its influence on the GDP growth rate that are in line with the results obtained by S. T. Nene, D. I. Kehinde and S. Mashapa (2022) in their research done in the selected European and African countries.…”
Section: Discussionsupporting
confidence: 90%
“…The statistics show that, in Albania, where the IT regime was introduced in that period, the GDP still has unstable movement, whereas in Romania, it had the tendency to grow during the analyzed period. Certainly, as one of the reasons for different influences, the strategy for Serbia, Romania, Turkey and Albania can indicate various economic conditions, which is also pointed to in the research studies by S. T. Nene, D. I. Kehinde and S. Mashapa (2022). The results of this study show that there are different influences of the IT regime in terms of its influence on the GDP growth rate that are in line with the results obtained by S. T. Nene, D. I.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the identical results investigating the WB economies have been argued by Durguti et al (2021) that there is a positive association between these two variables. Whereas, the contradictory results of this study turn out to be with the author Nene et al (2022), where they have argued that in the countries of some African economies, they have a positive impact, while in the countries of Europe, they have a significant negative impact.…”
Section: Econometric Findingscontrasting
confidence: 87%
“…Rangasamy (2009) and Wolassa (2015) found that not only has IT had a significant impact on decreasing inflation persistence in SA, but IT has also been effective in decreasing inflation uncertainty. Nene et al (2022) compared African IT (SA and Ghana) and European IT (Poland and the Czech Republic) countries. They found that the IT policy significantly reduced inflation uncertainty in the European countries but was insignificant in reducing inflation uncertainty in SA.…”
Section: Literature Reviewmentioning
confidence: 99%